Autologous blood injection for the treatment of recurrent mandibular dislocation. Issue 8 (August 2015) - Coser, R.; da Silveira, H.; Medeiros, P.; Ritto, F.G.
Abstract The purpose of the present study was to evaluate the effectiveness of autologous blood injection in the treatment of recurrent temporomandibular joint dislocation. Eleven patients diagnosed with recurrent dislocation of the joint that could not be self-reduced, received bilateral injections of autologous blood in the superior joint compartment and pericapsular region. During a follow-up period ranging from 24 to 35 months (average 29.6 months), eight patients (72.7%) did not show new episodes of dislocation. The most advocated treatment for recurrent dislocation is eminectomy, which involves a skin incision, with the risk of damaging the facial nerve, requires general anaesthesia, and presents an average success rate of 85% according to the literature. Autologous blood injection is a simple, rapid, minimally invasive, and cost-effective technique, with a low possibility of complications, and is a feasible alternative treatment before surgical intervention.